Directed Metallation - Chatani, Naoto (Topics in Organometallic Chemistry,, 2007)
Directed metalation is recognized as one of the most useful methodologies for the regio- and stereoselective generation of organometallic species, the generation of which necessarily leads to the selective formation of organic products. Cyclometalation using Li, Mn, and Pd, and directed hydrometalation and carbometalation using Al and Zn, have been utilized for regio- and/or stereoselective synthesis for decades. Recently, a new chelation-assisted methodology has been developed not only for controlling regio- and stereoselectivity of reactions, but also for accelerating reactions. In particular, chelation-methodology has been utilized as a new activation method, in which a carbon-metal bond is generated directly from a C-H bond; a reaction rarely achieved using conventional methods. A wide variety of catalytic functionalization reactions of C-H bonds by the utilization of a chelation, have been developed recently and are comprehensively discussed in this book by leading experts. In addition, new approaches to directed hydrometalation and directed carbometalation as a key step are also discussed. A unique stereo- and regioselective hydroformylation has been developed through the utilization of directed hydrometalation. The regioselective Mizoroki-Heck reaction is another example in which directed carbometalation can be used to achieve a high regioselectivity. These examples emphasize how these innovative methodologies are contributing to different fields of chemistry.